THU0151 RISK OF MALIGNANCIES ASSOCIATED WITH CS DMARDS IN RHEUMATOID ARTHRITIS: COMPARISON WITH GENERAL POPULATION AND BIOLOGIC TREATED PATIENTS (ANALYSIS OF A NATIONAL CLAIM DATABASE). (2nd June 2020) - Seror, R.; Lafourcade, A.; De-Rycke, Y.; Fautrel, B.; Mariette, X.; Tubach, F.
Abstract : Background: Objectives: To estimate the incidence rate of malignancies in csDMARD-treated RA patients and to compare it to that of general population and to biologic-treated RA patients Methods: We conducted an historical cohort study within the national claim database that prospectively records individual health resource use of 86% of the French population (65 million inhabitants). RA adult patients were identified based on ICD-10 code (M05 or M06) between 2007-2016. Patients with previous cancer history were excluded. Treatment exposures were incident first use of any treatment: csDMARD (methotrexate, leflunomide, sulfasalazine, azathioprine, hydroxychloroquine) or biologics (anti-TNF, rituximab, abatacept, tocilizumab, ustekinumab, anakinra). To identify incident treatment periods, only patients who did not receive any treatment in the 1-year period before the index date were selected. Exposure was defined with a 90-day latency after treatment initiation and a 180-day carry-over period after drug discontinuation. To compare the risk of malignancies between csDMARD-treated patients and general population, standardized incidence ratio (SIR [95%CI]) were calculated using FRANCIM ("France Cancer Incidence et Mortalité") estimations as reference. To compare the risk of malignancies between csDMARD and biologics treated patients, a dynamically propensity score (including age, sex, year of first occurrence of RA code, date of treatment initiation, number of previous DMARDs, Charlson's comorbidity index, diagnosis of tobacco and/or alcohol-associated disorders, number of hospitalizations for RA, cumulative corticosteroid dose) was constructed using pooled logistic regression. Hazard Ratios (HRs) for risk of cancer were estimated using Cox proportional hazards model after dynamically propensity score matching. Exposure was considered as a time-dependent variable. Results: Between 2007 and 2016, 83, 706 RA patients exposed to csDMARD (n=63, 837) and/or biologics (n=19, 727) were identified. As compared to the general population, csDMARDs treated patients had an increased risk of lung cancer (SIR=1.29 [1.14; 1.45]), invasive melanoma (SIR=1.52 [1.24; 1.86]) and a borderline increased risk of breast cancer (SIR=1.11 [1.01;1.22]). By contrast, they had a decreased risk of pancreatic cancer (SIR=0.68[0.51-0.9]) and liver cancer (SIR=0.43 [0.27; 0.67]). This later is due to a protopathic bias. After propensity score matching, analyses the risk of malignancies between csDMARD and biologics treated patients were conducted on 19727 patients in each group (mean age: 51 ±14 yrs; female: 74.6%). Malignancies occurred in 435 patients exposed to biologics and 332 patients exposed to csDMARD. The overall risk of malignancies (figure), risk of solid cancer (excluding non-melanoma skin cancer), lymphoma, and other hematologic malignancies did not differ significantly between csDMARD and all biologics (table). Regarding organ specific cancer, no difference was observed. Results were similar for biologic in monotherapy or associated with csDMARD. Conclusion: Using a large nationwide representative healthcare database, the overall risk of malignancies and the risk of organ-specific cancers and hematologic malignancies in biologic treated RA patients did not differ from that of patients treated with csDMARD. Compared to general population, patients treated with csDMARD had an increased risk of lung cancer and melanoma, but a decreased risk of pancreatic cancer. Disclosure of Interests: Raphaèle Seror Consultant of: BMS, Medimmune, Novartis, Pfizer, GSK, Lilly, Alexandre Lafourcade: None declared, yann de-rycke: None declared, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB, Xavier Mariette Consultant of: BMS, Gilead, Medimmune, Novartis, Pfizer, Servier, UCB, Florence Tubach Grant/research support from: Florence TUBACH is head of the Centre de Pharmacoépidémiologie (Cephepi) of the Assistance Publique – Hôpitaux de Paris and of the Clinical Research Unit of Pitié-Salpêtrière hospital, both these structures have received research funding, grants and fees for consultant activities from a large number of pharmaceutical companies, that have contributed indiscriminately to the salaries of its employees. Florence Tubach didn't receive any personal remuneration from these companies.